2018
DOI: 10.1002/lsm.23003
|View full text |Cite
|
Sign up to set email alerts
|

1.7 micron optical coherence tomography for vaginal tissue characterization in vivo

Abstract: The significantly improved performance of the novel 1.7 μm OCT imaging system demonstrates its potential use as a minimally-invasive monitoring tool of vaginal health in gynecologic practice. Lasers Surg. Med. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
(23 reference statements)
1
19
0
Order By: Relevance
“…In addition, diagnostic accuracy is limited by sample number and size [92][93][94]. To address the limitations of a conventional colonoscopy, endoscopic US, OCT, NIRF, and multiphoton have been applied in the GI tract to visualize the layered architecture and microvasculature, detect early stage disease, and assess treatment response with exogenous optical contrast agents, which represents a significant step toward noninvasive comprehensive characterization of GI disease [3,38,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111]. However, one of the key parameters, SO 2 saturation, is still lacking.…”
Section: Gi Tract Applicationmentioning
confidence: 99%
“…In addition, diagnostic accuracy is limited by sample number and size [92][93][94]. To address the limitations of a conventional colonoscopy, endoscopic US, OCT, NIRF, and multiphoton have been applied in the GI tract to visualize the layered architecture and microvasculature, detect early stage disease, and assess treatment response with exogenous optical contrast agents, which represents a significant step toward noninvasive comprehensive characterization of GI disease [3,38,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111]. However, one of the key parameters, SO 2 saturation, is still lacking.…”
Section: Gi Tract Applicationmentioning
confidence: 99%
“…To further optimize the performance of OCT devices, several studies have reported that OCT devices with a light source centered at 1.7 µm demonstrsted improved penetration depth by up to ~25% through ex-vivo or in-vivo tests [31][32][33]. The imaging depth of OCTA, which is based on OCT, is therefore also enhanced, allowing for mapping vasculature in deeper layers of biological tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] There are few groups that attempted to use OCT in female reproductive organs but their focus is mainly on cervix, fallopian tube, vagina, and recently on ovary. [10][11][12][13][14][15][16] Kirillin et al demonstrated accuracy of OCT in Editor: Shogo Hayashi.…”
Section: Introductionmentioning
confidence: 99%